Tunnelling through a GaAs/(AlGa)As coupled double-quantum well heterostructure - Velasquez, Robert (2002)
A splitting of the main resonant peales is observed in the current-voltage characteristics of a double-quantum-well resonant tunnelling device, due to coupling between well states. Under a high magnetic field applied in the current direction, the peales collapse into a single peak and from the magnetotunnelling data we are able to estimate the energy splitting between the coupled states © 2002 CSI. All rights reserved